Investigation on jet grouting support strategy for controlling time‐dependent deformation in the roadway. Issue 6 (18th February 2020) - Sun, Yuantian; Li, Guichen; Zhang, Junfei
Abstract: The efficiency of coal mining is seriously affected by roadway stability, as large time‐dependent deformation of roadway frequently occurs and needs to be maintained several times during its service life. Such rheological deformation was common in soft coal mass at Huaibei coalfield in China. To address this issue, in this study, the time‐dependent deformation of the soft coal roadway was analyzed and a new Jet Grouting (JG) technique was presented for controlling deformation. The time‐dependent deformation of the soft coal roadway was numerically simulated and validated. Based on the field test results and the verified model, a JG support model was established to examine its effect on roadway deformation. The JG support system can reduce the horizontal and vertical displacement of the roadway effectively and constrain the time‐dependent deformation of coal mass. The deformation rate and stabilization time of roadway decreased significantly by comparison with conventional support. This work presented a promising JG support scheme for controlling the time‐dependent deformation in the roadway in deep underground mine, which can greatly promote the JG design and application. Abstract : We first revealed the time‐dependent behavior of roadway in the deep underground coal mine. A high‐efficiency jet grouting technique on controlling rheological deformation was first evaluated by a time‐dependent 3D numerical model. The results are encouraging and the pioneering work can improve the safety of the coal roadway and the efficiency of coal mining.